2003
DOI: 10.1210/en.2002-220622
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptionally Active Human Type II Gonadotropin-Releasing Hormone Receptor Gene Homolog Overlaps Two Genes in the Antisense Orientation on Chromosome 1q.12

Abstract: GnRH-II peptide hormone exhibits complete sequence conservation across vertebrate species, including man. Type-II GnRH receptor genes have been characterized recently in nonhuman primates, but the human receptor gene homolog contains a frameshift, a premature stop codon (UGA), and a 3' overlap of the RBM8A gene on chromosome 1q.12. A retrotransposed pseudogene, RBM8B, retains partial receptor sequence. In this study, bioinformatics show that the human receptor gene promoter overlaps the peroxisomal protein 11-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 73 publications
2
92
0
5
Order By: Relevance
“…It may be that one acts as a hormone secreted into the blood circulation and one as a neuropeptide, in analogy with that found in brain, but this has to be further studied. Different receptors for GnRH 1 and 2 have been described in mammals although GnRH-R2 is not expressed as a fully functional receptor, due to a genomic stop sequence/frame shift [22,23]. However, both GnRH1 and GnRH2 are able to signal through the type 1 receptor [19].…”
Section: Discussionmentioning
confidence: 99%
“…It may be that one acts as a hormone secreted into the blood circulation and one as a neuropeptide, in analogy with that found in brain, but this has to be further studied. Different receptors for GnRH 1 and 2 have been described in mammals although GnRH-R2 is not expressed as a fully functional receptor, due to a genomic stop sequence/frame shift [22,23]. However, both GnRH1 and GnRH2 are able to signal through the type 1 receptor [19].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, attempts to clone and sequence of a full-length human GnRH-II receptor have not been successful (13). Morgan et al (14) found that the human GnRH-II receptor is expressed as a variety of splice variants and a functional human GnRH-II receptor transcript was not found. The GnRH-II receptor-like mRNA detected in this and in our previous study (6) is suspected to be non-functional because of the stop codon in the sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, analysis of DNA sequence data and functional studies indicate that there has been sporadic silencing or deletion of GnRH II and/ or the type II receptor in various mammals. Thus, GnRH I and GnRH II and the type I and type II GnRH receptors are expressed in some primates such as the marmoset [94] and green monkey while the type II GnRH receptor has been silenced in man and the chimpanzee by stop codons and frame shifts [101]. From a molecular genetics point of view, it is possible that, during evolution, the mammalian type II GnRH receptor gene came under functional pressure by close apposition of 5′ and 3′ anking genes (potentially leading to interference with transcription) and subsequent mutations led to gene silencing.…”
Section: Silencing Of Gnrhs and Gnrh Receptors In Mammalsmentioning
confidence: 99%